Metal-coordination polymers (John Wiley & Sons, 2005)
This series provides a useful, applications-oriented forum for the next generation of macromolecules and materials. The fifth volume in this series provides useful descriptions of the transition metals and their applications. Transition Metals are covered in 2 volumes, the second part is covered in Volume 6